Creation of Investment Funds in Ukraine by Individuals as a Criterion for Sustainable Development of the Country's Economy - Morhachov, Illia; Ovcharenko, Ievgen; Ivchenko, Yevgen; Buchniev, Maxym; Tkachenko, Nataliia; Derzhak, Nataliia (European Journal of Sustainable Development, 2021)
The article substantiates the hypothesis that the creation of investment funds by individuals in the country can be considered as a criterion for the existence of conditions of sustainable development of its economy. By example of Ukraine clarifies the issue of creating investment funds by individuals, in particular in terms of motives, feasibility, economic feasibility, problems and ways to solve the latter. For the conditions of Ukraine as an important factor in the feasibility of creating an investment fund by an individual identified the possibility of ensuring the transfer of inheritance to the heirs under national law. The stages of creation and development of the studied subjects are identified, which can be considered as "pain points" when considering the conditions of sustainable development in the country. The absence of facts of crossing these points in Ukraine by the studied subjects indicates the lack of conditions for sustainable development in the country. The refusal of the share form at the stage of existence of the limited liability company is substantiated, as well as the need to combine investment activities with others that are not capital-intensive given the high level of complexity and capital intensity of the researched business.